Politik Pengetahuan Kolonial dalam Relasi Guru dan Murid di Hindia Belanda: : Hubungan Snouck Hurgronje dan Hoesein Djajadiningrat - Mohammad Refi Omar Ar Razy (Badan Riset dan Inovasi Nasional (BRIN), 2026)
This article examines the politics of colonial knowledge as it operated through teacher–student relations within the educational context of the Dutch Indies, focusing on the relationship between Snouck Hurgronje and Hoesein Djajadiningrat as a primary case study. The aim of this study is to analyze Snouck’s motives in maintaining a long-term relationship with his indigenous student, to identify the personal dimensions that extended beyond formal academic relations, and to explore how this relationship shaped Hoesein’s intellectual orientation and career choices. The main sources consist of correspondence between Snouck and Hoesein from 1913 to 1935, institutional archives, and contemporary publications. The findings demonstrate that the relationship between Snouck and Hoesein was not neutral, but functioned as a crucial mechanism in the production, validation, and circulation of colonial knowledge. This relationship was sustained not only through academic supervision but also through personal bonds, financial patronage, and symbolic recognition that reinforced intellectual loyalty. Furthermore, Hoesein’s transition from an academic trajectory to the colonial bureaucracy reveals the ambivalence of the colonial education project, which succeeded in producing educated elites but failed to fully control the ways in which knowledge was ultimately deployed. This study concludes that colonial education operated as a system of social relations that intertwined knowledge, power, and emotion in the formation of modern indigenous elites.